Organic carbon content controls the severity of water repellency and the critical moisture level across New Zealand pasture soils - Hermansen C; Moldrup P; Müller K; Jensen PW; van den Dijssel C; Jeyakumar P; de Jonge LW (Elsevier BV)
Organic matter can render soil hydrophobic and cause soil water repellency (SWR) which has large implications for agriculture. Consequences such as fingered flow, uneven wetting patterns, and increased overland flow reduce irrigation efficiency and plant nutrient availability. The phenomenon of SWR is a transient soil property depending, inter alia, on soil water content (w). Soil can exhibit SWR from oven-dry w until the critical w where it again becomes fully wettable (wNON). The total SWR can be obtained from the nonlinear SWR-w relationship as the integrated trapezoidal area under the SWR-w curve (SWRAREA). We analyzed 78 soil samples, representing five dominant soil orders in the South Island of New Zealand. The soils had a large range in clay (0.000–0.520 kg kg−1) and organic carbon (OC) content (0.021–0.217 kg kg−1). The degree of SWR was measured on soils at air-dry conditions (SWRAD) and after heat-pretreatment at 60 (SWR60) and 105°C (SWR105). Further, SWR was measured in small w increments above air-dry w until wNON was reached. The SWR-w curves were either unimodal or bimodal, or no SWR occurred. SWRAREA ranged from 0.16 to 26.82 mN m−1 kg kg−1. Among the five soil orders tested, the Podzols exhibited the highest severity in SWR, whereas the Semiarid soils were the least hydrophobic soils. In conclusion, OC was the main factor for controlling the severity of SWR. Though, pH also had minor effects on SWR. Further, an upper limit critical water content was derived from the simple relationship between the wNON and OC, which could be applied to improve irrigation practices of pastoral soils. However, there is a need for further testing on different soils and land uses.
Keywords: 05 Environmental Sciences; 06 Biological Sciences; 07 Agricultural and Veterinary Sciences